Pengaruh Yoga terhadap Tekanan Darah pada Remaja Putri yang Mengalami Kegemukan di SMPN 2 Jetis Kabupaten Bantul - Anggi Afida Wahyu; Dwi Yulinda (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
Teenagers have a greater risk of being overweight than other age groups. Rates of diseases such as heart disease, type 2 diabetes mellitus (DM), and high blood pressure also increase along with obesity, and all three have the potential to become degenerative diseases in the future. Obesity in adolescents is associated with increased blood pressure. Yoga can help hypertensive patients reduce their anxiety and blood pressure. Yoga is one of the best ways to get in shape and reduce your body mass index and waist size. The design in this study uses a quasy experimental design. Using a time series approach with a comparison group (control time series design) with a pretest posttest control group. The sampling technique used purposive sampling with a total sampling of 15 people in the treatment group and 15 people in the control group. Blood pressure measurement using a sphighmomanometer. Data analysis used the Pairet T-test. The study showed that there was an effect of yoga on blood pressure in female adolescents who were overweight both systolic and diastolic with the statistical significance of the Mann Whitney U p-value: 0.010 and 0.016 (<0.05). Conclusion: this study has the effect of yoga on blood pressure in overweight female adolescents at SMPN 2 Jetis, Bantul Regency